PENGARUH KONTEN “RYZEN” DI APLIKASI NIMO TV TERHADAP SIKAP BERMAIN GAME PUBG MOBILE SEA ESPORT - Kamal, Ahmad; Sopyan, Muhamad (Transpublika Publisher, 2023)
This study aims to determine whether there is an effect of “Ryzen”on Nimo TV content on the attitude of playing PUBG Mobile games SEA Esport. This research makes SEA Esport members as respondents. The theory used in this research is hypodermic needle theory and this research also uses quantitative-descriptive methods. The results of this study are that Ryzen” on Nimo TV content can affect the attitude of playing PUBG Mobile games. In addition, testing using other variables, regarding a person's motivation to use the media, because from the results of this study only 49% of the influence of X on Y. The results of this study can also be a recommendation for content planners for Nimo TV Indonesia if they have adequate resources to create and To develop content, Nimo TV Indonesia shows must always be packaged in an attractive manner, and provide information on how to play games.